Reversible Second Order Kinetics of Sorption-Desorption of Cr(VI) Ion on Activated Carbon from Palm Empty Fruit Bunches - Iip Izul Falah; Ruliatima Ruliatima; Triyono Triyono (Universitas Gadjah Mada, 2015)
Activated carbon (AC) from palm empty fruit bunches has been prepared, and this material was then used to adsorb Cr(VI) from a solution. Characterization of the AC was conducted by detection of its functional groups, determination of total volatile compounds (VC) content and its iodine number. Study on sorption-desorption kinetics was conducted by comparing results of evaluations of several models with proposed reversible second order model using the data produced in this work. Results of the works showed that the AC had similar characters compared with the AC produced by previous researchers. Application of the kinetics models on sorption Cr(VI) onto the AC showed that nearly all of the models gave a good linearity. However, only the proposed model had a good relation with Langmuir isotherm, with respectively sorption (ks) and desorption (kd) constants were 5.75 x 10-4 L.mg‑1.min-1 and 2.20 x 10-3 min-1; maximum sorption capacity, qm = 20.00 mg.g-1; and equilibrium constant, K from kinetics experiment (0.261 L.mg-1) was comparable with the result from the isotherm experiment (0.269 L.mg-1). Hence, using this model, kinetics and Langmuir parameters can probably be determined from a single kinetics data experiment.